Margret & H.A. Rey's Curious George feeds the animals - Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Vipah Interactive (Boston : Houghton Mifflin, 1998)
Curious George gets in trouble by feeding the animals at the zoo, but when a parrot escapes from the rainforest exhibit he is able to save the day.
"Based on the character of Curious George created by Margret and H.A. Rey"--T.p. verso.
Spine title: Curious George feeds the animals.
3.5
K-3
K-3
L.A. Recommended Foreign Language
Keywords: Curious George (Fictitious character) -- Fiction; Monkeys -- Fiction; Zoos -- Fiction; Parrots -- Fiction; Curious George (Fictional character) -- Fiction; Monkeys -- Fiction; Zoos -- Fiction; Parrots -- Fiction